Syntheses and Structures of Xenon Trioxide Alkylnitrile Adducts. (30th September 2016) - Goettel, James T.; Matsumoto, Kazuhiko; Mercier, Hélène P. A.; Schrobilgen, Gary J.
Abstract: The potent oxidizer and highly shock‐sensitive binary noble‐gas oxide XeO3 interacts with CH3 CN and CH3 CH2 CN to form O3 XeNCCH3, O3 Xe(NCCH3 )2, O3 XeNCCH2 CH3, and O3 Xe(NCCH2 CH3 )2 . Their low‐temperature single‐crystal X‐ray structures show that the xenon atoms are consistently coordinated to three donor atoms, which results in pseudo‐octahedral environments around the xenon atoms. The adduct series provides the first examples of a neutral xenon oxide bound to nitrogen bases. Raman frequency shifts and Xe−N bond lengths are consistent with complex formation. Energy‐minimized gas‐phase geometries and vibrational frequencies were obtained for the model compounds O3 Xe(NCCH3 ) n ( n =1–3) and O3 Xe(NCCH3 ) n ⋅[O3 Xe(NCCH3 )2 ]2 ( n =1, 2). Natural bond orbital (NBO), quantum theory of atoms in molecules (QTAIM), electron localization function (ELF), and molecular electrostatic potential surface (MEPS) analyses were carried out to further probe the nature of the bonding in these adducts.